On fuzzy self-adaptive PID control for USV course - Yunsheng, Fan; Xiaojie, Sun; Guofeng, Wang; Chen, Guo (2015 34th Chinese Control Conference (CCC), 2015)
The course control system of an unmanned surface vehicle (USV) is a complex system with time-varying, nonlinear and multi-disturbances. Combining with PID control and fuzzy logic, a kind of fuzzy self-adaptive PID control algorithm for USV course control is put forward. Based on the turning test of the USV "Lanxin" of Dalian Maritime University, simulation parameters of 3-DOF maneuvering mathematical model for the "Lanxin" USV planar motion are compared and analyzed, and a fuzzy self-adaptive PID control algorithm of the USV course control is proposed, and the self-adaptive fuzzy parameter tuning rules for PID course controller are given, so as to realize the online self-tuning of the controller parameters. Finally, simulation results show that the fuzzy self-adaptive PID USV course control possesses good dynamic response comparing with the conventional PID control with the disturbances of wind, wave and current. It was found that better robustness should appear to the parameter perturbation and external disturbances.